A New Method for Measuring Organizational Authority and Accountability: Quantitative Approach - Jevtić, Miloš Vladimir; Jovanović, Milica Milorad; Krivokapić, Jovan (Industrija, 2018)
This paper suggests a new approach to measuring the alignment of authority and accountability of different positions within an organization. According to the controllability principle, accountability and authority should be aligned for achieving better organizational results. Nevertheless, there is still a research gap in the quantification of this alignment. Thus, this paper aims to improve the method of measuring authority and accountability. It proposes a new approach to measuring authority and accountability, as well as the rules for defining their alignment. The suggested model is tested through the research conducted in 241 organizations. Top managers from the organizations answered the structured questionnaire. The results show statistically significant dependence between the alignment of authority and accountability and organizational performance. In order to overcome the identified limitations of the conducted research, it is necessary to do some additional research to verify general applicability of the proposed approach.
Keywords: Organization; Authority; Account